Hypothalamic dopamine is required for salsolinol‐induced prolactin secretion in goats. (29th May 2017) - Hashizume, Tsutomu; Watanabe, Ryunosuke; Inaba, Yuki; Sawai, Ken; Fülöp, Ferenc; Nagy, György Miklos
Abstract: The aim of the present study was to clarify the relationship between hypothalamic dopamine (DA) and salsolinol (SAL) for the secretion of prolactin (PRL) in goats. SAL or thyrotropin‐releasing hormone (TRH) was intravenously injected into female goats treated with or without the D2 DA receptor antagonist haloperidol (Hal), which crosses the blood‐brain barrier, and the PRL‐releasing response to SAL was compared with that to TRH. PRL‐releasing responses to SAL, Hal, and Hal plus SAL were also examined after a pretreatment to augment central DA using carbidopa (Carbi) and L‐dopa. The PRL‐releasing response to Hal alone was greater than that to SAL or TRH alone. The PRL‐releasing response to Hal plus SAL was similar to that of Hal alone. In contrast, the PRL‐releasing response to Hal plus TRH was greater than that to TRH or Hal alone. The treatment with Carbi plus L‐dopa inhibited SAL‐ and Hal‐induced PRL secretion. The inhibition of the PRL‐releasing response to SAL disappeared when SAL was injected with Hal. These results indicate that the mechanisms underlying the SAL‐induced PRL response differ from those of TRH, and suggest that hypothalamic DA and its synthesis is associated in part with SAL‐induced PRL secretion in goats.